2008
DOI: 10.1007/s00464-008-9981-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open ventral hernia repairs: 5 year recurrence rates

Abstract: This is the first study to compare 5 year actual recurrence rates between laparoscopic and open ventral hernia repairs. Contrary to prior reports, our longer-term data indicates similar recurrence rates, except for higher rates in the laparoscopic converted to open group. Due to the continued recurrences over the period studied, longer-term follow-up is necessary to appreciate the true rate of hernia recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 18 publications
3
35
1
2
Order By: Relevance
“…Therefore, 15 observational trials with 2452 patients qualified for meta-analysis according to the study's inclusion criteria. [1327]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 15 observational trials with 2452 patients qualified for meta-analysis according to the study's inclusion criteria. [1327]…”
Section: Resultsmentioning
confidence: 99%
“…Since Leblanc et al [8] reported the first LVHR in 1992, this technique has generated significant interest with its reduced LOS, and lower rate of wound complications and recurrence rates [9][10][11][12]. These benefits, however, are offset by higher risk of procedure-related complications, especially unrecognized hollow viscous injury, which can lead to sepsis and death [13].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate (4.4-29 %) mentioned in the recent reports on sIPOM [12][13][14][43][44][45] has been quite variable, which is attributable to the differences in the size of the hernial orifice and body mass index (BMI) of the patients and the differences in the follow-up periods. A simple comparison of the surgical outcomes of IPOM-Plus with sIPOM is meaningless because of the absence of large prospective randomized studies on the recurrence or complication rates of IPOM-Plus and sIPOM.…”
Section: Recurrencementioning
confidence: 96%